Preclinical modeling in glioblastoma patient-derived xenograft (GBM PDX) xenografts to guide clinical development of lisavanbulin—a novel tumor checkpoint controller targeting microtubules. Issue 3 (7th July 2021) - Burgenske, Danielle M; Talele, Surabhi; Pokorny, Jenny L; Mladek, Ann C; Bakken, Katrina K; Carlson, Brett L; Schroeder, Mark A; He, Lihong; Hu, Zeng; Gampa, Gautham; Kosel, Matthew L; Decker, Paul A; et al.
Abstract: Background: Glioblastoma (GBM) is an incurable disease with few approved therapeutic interventions. Radiation therapy (RT) and temozolomide (TMZ) remain the standards of care. The efficacy and optimal deployment schedule of the orally bioavailable small-molecule tumor checkpoint controller lisavanbulin alone, and in combination with, standards of care were assessed using a panel of IDH-wildtype GBM patient-derived xenografts. Methods: Mice bearing intracranial tumors received lisavanbulin +/−RT +/−TMZ and followed for survival. Lisavanbulin concentrations in plasma and brain were determined by liquid chromatography with tandem mass spectrometry, while flow cytometry was used for cell cycle analysis. Results: Lisavanbulin monotherapy showed significant benefit ( P < .01) in 9 of 14 PDXs tested (median survival extension 9%-84%) and brain-to-plasma ratios of 1.3 and 1.6 at 2- and 6-hours postdose, respectively, validating previous data suggesting significant exposure in the brain. Prolonged lisavanbulin dosing from RT start until moribund was required for maximal benefit (GBM6: median survival lisavanbulin/RT 90 vs. RT alone 69 days, P = .0001; GBM150: lisavanbulin/RT 143 days vs. RT alone 73 days, P = .06). Similar observations were seen with RT/TMZ combinations (GBM39: RT/TMZ/lisavanbulin 502 days vs. RT/TMZ 249 days, P = .0001; GBM26: RT/TMZ/lisavanbulin 172 days vs. RT/TMZ 121 days, P = .04). Immunohistochemical analyses showed a significant increase in phospho-histone H3 with lisavanbulin treatment ( P = .01). Conclusions: Lisavanbulin demonstrated excellent brain penetration, significant extension of survival alone or in RT or RT/TMZ combinations, and was associated with mitotic arrest. These data provide a strong clinical rationale for testing lisavanbulin in combination with RT or RT/TMZ in GBM patients.